2013
DOI: 10.2485/jhtb.22.189
|View full text |Cite
|
Sign up to set email alerts
|

Amelogenin in Frog Species, Xenopus tropicalis: A Gene Evolutionary Approach

Abstract: The structure and function of the amelogenin gene on a tooth germs in the frog Xenopus tropicalis, were examined. Using PCR, we observed an intensive band of amelogenin in maxillas with teeth but not in the toothless mandibles, and in situ hybridization revealed the restricted expression of amelogenin only in secreting ameloblasts in a tooth germs. Sequence analyses indicated that two types of amelogenin mRNA were alternatively spliced and derived from a single gene. They are referred to here as amelogenin mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In amphibians, for instance, the aprismatic enamel contains no sulfated glycoconjugates, whereas they are present in the prismatic enamel of mammals (23,24). Amelogenin genes have been detected in various amphibians and reptiles (13)(14)(15)(16)(17)(18)(19) (Figure 5). Ishiyama et al (13) only detected 56% homology between the amelogenin gene nucleotide sequences of mammals and reptiles, whereas 90% homology was observed amongst mammalian amelogenin genes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In amphibians, for instance, the aprismatic enamel contains no sulfated glycoconjugates, whereas they are present in the prismatic enamel of mammals (23,24). Amelogenin genes have been detected in various amphibians and reptiles (13)(14)(15)(16)(17)(18)(19) (Figure 5). Ishiyama et al (13) only detected 56% homology between the amelogenin gene nucleotide sequences of mammals and reptiles, whereas 90% homology was observed amongst mammalian amelogenin genes.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that intense immunoreactivity to anti-mammalian amelogenin antibodies was observed in the collar enamel of Lepisosteus (4,12), implying that amelogenin-like proteins are present. However, no amelogenin gene has yet been detected in fish, while amelogenin genes have been discovered and sequenced in mammals, reptiles and amphibians (13)(14)(15)(16)(17)(18)(19). There is little available knowledge about fish enamel matrix proteins.…”
Section: Introductionmentioning
confidence: 93%